Tropical tree for urban environment: their microclimatic properties - Shahidan, Mohd Fairuz; Mohd Shariff, Mustafa Kamal; Hon, Beatrice Jia Qi (Universiti Putra Malaysia Press, 2016)
Trees have always been a major element in urban landscape design. Formerly, the existence of trees in landscape design focused on the aesthetic and functional aspects of trees in offering better urban living environments. By understanding the thermal performances of these tropical trees, they can be appropriately used in planting design and the suitable implementation of tree planting scheme could be achieved. The combination of trees, technical and physiology aspects in this handbook will guide designers in achieving environmental design quality by focusing on climate adaptation and microclimate improvement through the right choice of landscape trees. Given the environmental contributions of trees to the environment especially towards human thermal comfort in tropical climate, knowledge that contribute to the proper selection of trees species for thermal performances is essential for landscape architects, architects and other related urban professionals as well as to interested urban residents.